Halloween cupcake murder - O'Connor, Carlene; Ireland, Liz; Perry, Carol J. (O'Connor, Carlene. Irish village mystery, 2023)
HALLOWEEN CUPCAKE MURDER by CARLENE O'CONNOR. With Galway's Halloween Mystery Tour only a few days away, Tara Meehan is scouring the town's curiosity shops for spooky decorations to draw tourists into her architectural salvage store. But when a stranger appears in her shop bearing a cryptic cupcake and an ominous message, Tara suddenly finds herself tangled in a mystery with ancient Gaelic roots, but very modern--and very deadly--consequences . . .